Factors In The Aspect Of Regional Financial Management Regarding The Budget Over Remains (Silpa) At The Gowa District Education Service - Saskia, Saskia; Sultan Sarda; Masrullah, Masrullah (CV. AFDIFAL MAJU BERKAH, 2024)
This type of research uses a descriptive method with a qualitative approach, which aims to determine the factors in the Regional Financial Management Aspect of the Surplus Budget Calculation (SILPA) at the Gowa Regency Education Office. This research was carried out at the Gowa Regency Education Office which took place from 30 April 2024 to 30 May 2024. This sample was taken from the Gowa Regency Education Office. The types of data used in this research are secondary data and primary data. Data collection was carried out by observation, interviews and documentation. In this research, the data sources used in data collection include subject data, physical data, documentary data. The research instruments used in this research used survey, observation and literature review methods. Based on the research results, data was obtained through in-depth interviews, observations and documentation, where all the informants who conducted in-depth interviews were the head of the Gowa Regency Education Office, Head of the General and Personnel Subdivision, Head of the Financial Accounting Subdivision and Secretary of the Gowa Regency Education Office regarding factors. Factors in the Regional Financial Management Aspect of Over Remaining Budget Calculations (SILPA) at the Gowa Regency Education Service which was discussed previously, the author draws the conclusion that with careful planning, structured administrative records, and increasing human resource competency, the Gowa Regency Education Office has made efforts to reduce the occurrence of SILPA.